Novel random peptide libraries displayed on AAV serotype 9 for selection of endothelial cell-directed gene transfer vectors - Varadi, Karl; Hecker, Markus; Katus, Hugo; Müller, Oliver J. (Gene therapy, 2012)
We have demonstrated the potential of random peptide libraries displayed on adeno-associated virus (AAV)2 to select for AAV2 vectors with improved efficiency for cell type-directed gene transfer. AAV9, however, may have advantages over AAV2 because of a lower prevalence of neutralizing antibodies in humans and more efficient gene transfer in vivo. Here we provide evidence that random peptide libraries can be displayed on AAV9 and can be utilized to select for AAV9 capsids redirected to the cell type of interest. We generated an AAV9 peptide display library, which ensures that the displayed peptides correspond to the packaged genomes and performed four consecutive selection rounds on human coronary artery endothelial cells in vitro. This screening yielded AAV9 library capsids with distinct peptide motifs enabling up to 40-fold improved transduction efficiencies compared with wild-type (wt) AAV9 vectors. Incorporating sequences selected from AAV9 libraries into AAV2 capsids could not increase transduction as efficiently as in the AAV9 context. To analyze the potential on endothelial cells in the intact natural vascular context, human umbilical veins were incubated with the selected AAV in situ and endothelial cells were isolated. Fluorescence-activated cell sorting analysis revealed a 200-fold improved transduction efficiency compared with wt AAV9 vectors. Furthermore, AAV9 vectors with targeting sequences selected from AAV9 libraries revealed an increased transduction efficiency in the presence of human intravenous immunoglobulins, suggesting a reduced immunogenicity. We conclude that our novel AAV9 peptide library is functional and can be used to select for vectors for future preclinical and clinical gene transfer applications.